Effects of different coagulant enzymes used on quality of traditional Örgü cheese (Braided cheese) - Mehmet Çelebi; Bedia Şimşek (Mljekarstvo)
In this study, Örgü cheese has been produced by using different coagulating enzymes (calf rennet, microbial enzymes, recombinant chymosin). The effects of different coagulating enzymes which are used on the characteristic of mineral material and cheese has been observed during 90 days ripening time. Mineral material contents of Örgü cheese have been determined with ICP-OES (inductively coupled plasma optical emission spectroscopy). Proteolysis levels of cheese have been observed with chemical analysis and help of SDS-PAGE (sodium dodecyl sulfate polyacrylamide gel electrophoresis). The determined difference between analysis results, titratable acidity, total nitrogen, water soluble nitrogen, ripening index, total solid, fat, fat in total solid, salt, salt in total solid, ash, texture, mineral material (Ca, Fe, Cu, Al, Mg, Mn) of Örgü cheese’s analysis result haven’t been regarded as significant statistically. Each of enzymes which are used effects similarly on α-casein and β-casein during the ripening time and each of the ratios which are gained have been closely determined.